Are intrauterine growth restriction and preterm birth associated with dental caries? - Saraiva MCD, Bettiol H, Barbieri MA, Silva AA. (Blackwell Synergy, 2007)
To assess the association between two intrauterine growth restriction (IUGR) surrogates – IUGR [small for gestational age birth (SGA) and fetal growth restriction (FGR)] and preterm birth with dental caries.